2018
DOI: 10.5951/jresematheduc.49.2.0178
|View full text |Cite
|
Sign up to set email alerts
|

Loving and Loathing: Portrayals of School Mathematics in Young Adult Fiction

Abstract: Images of mathematics and mathematicians are often negative and stereotyped. These portrayals may work to construct our impressions of mathematics and influence students' identity with and future participation in the subject. This study examined young adult fiction as a context in which school mathematics is portrayed and constructed. I used positioning theory and the notion of story lines to analyze a sample of 59 books. Portrayals of school mathematics within this sample involved multiple story lines, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In one of the only thorough studies of its kind, Darragh () focused her analysis on 59 YA novels referencing the mathematics classroom. She found that school mathematics is positioned negatively in more than half ( n = 31) of them, followed by neutral ( n = 17), positive ( n = 7), and mixed ( n = 4).…”
Section: Mathematics Learning Experiences In Ya Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…In one of the only thorough studies of its kind, Darragh () focused her analysis on 59 YA novels referencing the mathematics classroom. She found that school mathematics is positioned negatively in more than half ( n = 31) of them, followed by neutral ( n = 17), positive ( n = 7), and mixed ( n = 4).…”
Section: Mathematics Learning Experiences In Ya Literaturementioning
confidence: 99%
“…This is entirely possible. It could very well take me eighty‐eight years to understand algebra” (from The True Meaning of Cleavage ; Fredericks, as cited in Darragh, , p. 185). Unsurprisingly, the depiction of mathematics class as to be avoided, confusing or difficult, and tense are prevalent in Darragh’s findings, adhering to an especially stubborn stigma and gatekeeping practices concerning in‐school mathematics‐learning contexts (Nasir & Hand, ).…”
Section: Mathematics Learning Experiences In Ya Literaturementioning
confidence: 99%
See 3 more Smart Citations